Pengaruh Digitalisasi Dan Inovasi Pelayanan Website Jakevo Terhadap Kepuasan Masyarakat Di Keluarahan Cempaka Putih Barat Kota Jakarta Pusat - Wahyuningsih, Wahyuningsih; Prabhata, Indra (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This study was motivated by the phenomenon of decreased in community satisfaction in West Cempaka Putih Sub- District the use of Jakevo's website reveals a fact on the ground, among others, that people are struggling to adjust to digital services that are expected to be quick and easy, while cooperation between various parties and previous digital experiences are the key to the success of this innovation. The population in this study was the people of Cempaka Putih Barat Subdistrict, totaling 37,476 people and the research sample was 100 respondents, the sampling technique used Purposive Sampling technique. Data analysis technique used is multiple linear regression analysis with SPSS for Windows Ver.26. The results of this study indicate that: (1) digitalization has a positive and significant effect of 73.3% on the variation of community satisfaction with a significance value of 0.000 (2) service innovation has a positive and significant effect of 67.3% on the variation of community satisfaction with a significance value of 0.000 (3) digitalization and service innovation has a positive and significant effect of 76.5% on the variation of community satisfaction with a significance value of 0.000